Hybrid digital authoritarianism in Turkey: the 'Censorship Law' and AI-generated disinformation strategy - Yucel, Alev (Routledge Journals, Taylor & Francis Ltd, 2025)
This article introduces the concept of hybrid digital authoritarianism, a model of digital governance that combines consolidated digital authoritarian practices with strategically limited digital freedoms to sustain a fa & ccedil;ade of democratic governance. The evolution of Turkey's digital governance, marked by the enactment of the 'censorship law/disinformation law' in October 2022, represents a deliberate shift toward more entrenched digital authoritarianism. The dissemination of pro-government AI-generated disinformation, particularly targeting opposition during the 2023 national and presidential elections and the 2024 local elections, underscores Turkey's progression towards a more consolidated form of digital authoritarianism. This study examines the impact of recent legislative changes, including the contentious Press Law and Internet Regulation Law, and the role of AI-generated disinformation in shaping Turkey's digital governance.
Keywords: Hybrid Digital Authoritarianism; Ai-Generated Disinformation; Censorship Law; Freedom Of Expression; Turkish Politics